Reinforcement learning : an introduction - Sutton, Richard S.; Barto, Andrew G. (Adaptive computation and machine learning series, 2018)
"Reinforcement learning, one of the most active research areas in artificial intelligence, is a computational approach to learning whereby an agent tries to maximize the total amount of reward it receives while interacting with a complex, uncertain environment. In Reinforcement Learning, Richard Sutton and Andrew Barto provide a clear and simple account of the field's key ideas and algorithms."--